Penerapan Permainan Labirin Kardus Untuk Meningkatkan Kecerdasan Visual Spasial Anak Usia Dini - Kencana, Rita (Asghar: Jurnal of Children Studies, 2025)
This study aims to determine the application of cardboard maze games in improving early childhood visual-spatial intelligence. Visual-spatial intelligence is the ability to understand and manipulate shapes, spaces, and relationships between objects that are very important for children's cognitive development. The research method used is This study uses a mixed method, namely qualitative and quantitative methods with the type of classroom action research, which was carried out in two cycles on 10 children aged 5–6 years at KB Ar-Rahman Tembilahan. Data were collected through observation of teacher activities, observation of children's activities, and visual-spatial intelligence tests. The results of the study showed a significant increase in each indicator. The percentage of learning implementation by teachers increased from 52% in the pre-cycle to 80% in the first cycle, and 90% in the second cycle. Children's activity also increased from 45% in the pre-cycle to 79% in the first cycle, and 85% in the second cycle. The results of the child's visual-spatial intelligence test increased from 36.66% in the pre-cycle to 65% in the first cycle, and 84.1% in the second cycle. These findings show that the application of cardboard maze games is effective in improving children's visual-spatial intelligence through fun and interactive learning activities. This study recommends teachers to use simple game-based media in learning as an effort to improve children's cognitive abilities.